Cost-effective opportunities for climate change mitigation in Indian agriculture - CGIAR Research Program on Maize (2019)
peer reviewed journal article presents mitigation measures and associated costs and benefits of adoption, derived from a variety of sources in the form of Marginal Abatement Cost Curves (MACC). We estimated that by 2030 a potential technical mitigation potential of 85.5 MtCO2e per year through adoption of various mitigation practices.